THE EFFECT OF REAL LEARNING (EDUTAINMENT) ON IMPROVING HEALTH LITERACY AND STUDENT LEARNING MOTIVATION AT X JUNIOR HIGH SCHOOL - Yessy Fitriani (Journal of Health Management, Administration and Public Health Policies, 2026)
Literacy and numeracy are essential competencies for elementary school students, yet learning is often dominated by conventional methods that limit student engagement. This study implemented an Edutainment-based learning approach using a literacy and numeracy snake and ladder game to improve students’ competencies. Participants were divided into three groups and engaged in gamebased learning activities involving literacy questions and numeracy challenges. The program was evaluated using a pretest–posttest design and observations of student participation. The results showed increased student engagement, enthusiasm, and collaboration throughout the learning process. Higher posttest scores compared to pretest scores indicated improvements in literacy and numeracy skills. Teachers and schools responded positively to the learning media. Therefore, the Edutainment-based literacy and numeracy snake and ladder game is an effective learning strategy to enhance student participation and support literacy and numeracy achievement in elementary schools.